(untitled) (Zaporizhzhia Historical Review, 2021)
Basing on the published and archival data, the article describes the process of delimitation of freedoms in Zaporozhian Troops and Don Troops during 1740-s; it was determined that the urgent need for the border stipulated the activity of the representative of Zaporozhian Quarters ñ Vasil Kishensky, Colonel of Mius Palanka; it was established that, despite the dissociation, the problem of ìdisputable landsî had not been solved.